FINANCIAL LEASING AS AN INVESTMENT INSTRUMENT OF FIXED ASSETS RENOVATION OF DOMESTIC ENTERPRISES - O. Miroshnychenko (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The main characteristics of the financial leasing using as an investment instrument for fixed assets renovation of domestic enterprises have been considered. The advantages of financial leasing and the need to use in order to update the fixed assets, especially in the lack of financial resources for the purchasing of new machinery and equipment, have been determined.